Isolation of a Novel Jumbo Bacteriophage Effective Against Klebsiella aerogenes - Lewis, Rhea; Clooney, Adam G.; Stockdale, Stephen R.; Buttimer, Colin; Draper, Lorraine A.; Ross, R. Paul; Hill, Colin (Frontiers in Medicine, 2020)
Increasing levels of bacterial resistance to many common and last resort antibiotics has increased interest in finding new treatments. The low rate of approval of new antibiotics has led to the search for new and alternative antimicrobial compounds. Bacteriophages (phages) are bacterial viruses found in almost every environment. Phage therapy was historically investigated to control bacterial infections and is still in use in Georgia and as a treatment of last resort. Phage therapy is increasingly recognised as an alternative antimicrobial treatment for antibiotic resistant pathogens. A novel lytic Klebsiella aerogenes phage N1M2 was isolated from maize silage. Klebsiella aerogenes is a member of the ESKAPE bacterial pathogens is an important target for new antimicrobial therapies. Klebsiella aerogenes can form biofilms on medical devices which aids its environmental persistence and for this reason we tested the effect of phage N1M2 against biofilms. Phage N1M2 successfully removed a pre-formed Klebsiella aerogenes biofilm. Biofilm assays were also carried out with Staphylococcus aureus and Phage K. Phage K successfully removed a preformed Staphylococcus aureus biofilm. Phage N1M2 and Phage K in combination were significantly better at removing a mixed community biofilm of Klebsiella aerogenes and Staphylococcus aureus than either phage alone.